Analysis of Tobin's Q, Market to Book Value of Equity and Profitability (ROA), on Asset Growth in Property Companies on the Indonesia Stock Exchange (IDX) - Sari Bulan Tambunan (Ilomata International Journal of Tax and Accounting, 2023)
This study aims to determine, analyze, and test Tobin's q, market-to-book value of equity and profitability (ROA), on asset growth in property companies on the Indonesia Stock Exchange (IDX). This study uses a quantitative descriptive approach with the support of a panel regression model, which is used as a predictive analysis tool. The sampling technique used a non-probability random sampling approach with a purposive sampling method. The results of this study indicate that the independent variables (Tobin's q (TQ), MBV, and ROA) both simultaneously or together and partially or individually have no effect on the dependent variable (asset growth). The R square value, or the coefficient of determination (R2), is 0.54. This shows the ability of Tobin's q (TQ), MBV, and ROA to explain the growth of assets of property companies listed on the Indonesia Stock Exchange by 54%, or, in other words, the ability of Tobin's q (TQ), MBV, and ROA to have an effect of 54% on asset growth variables. Meanwhile, the remaining 46% is influenced by other variables not discussed in this study.